A model for upper delta plain coals, south central West Virginia - Howell, David J.; University of South Carolina (1980)
The Upper Pennsylvanian Allegheny of southern West Virginia consists principally of graywacke sandstone, with subordinate amounts of finer grained clastics and coals. Previous workers, notably Cavaroc and Ferm, have interpreted these rocks as forming in a Upper Delta Plain environment, in which coals are deposited in interdistributary areas. This study was divided in three parts. Firstly, previous literature was reviewed. Cavaroc's model includes en echelon stacking of successive sandstone bodies, but few details of coal body geometry. Work of FIsk on the Mississippi River described a peat body, with Upper Delta Plain affinities, which exhibited splitting by contemporaneous crevasse splay systems. Secondly, the en echelon sandstone model of Cavaroc was checked using previously unavailable closely spaced borehole information. Lastly, three separate Upper Delta Plain coal bodies were examined to show their principal features and mutual affinities.
Each coal body is greater than 20,000 feet in any dimension, and becomes thin, (a) by splitting due to intrusions of crevasse splays from surrounding channel systems, (b) by gradual thinning of unknown cause, or (c) by cutouts due to overlying sandstone channel systems. It was found that the influence of surrounding contemporaneous crevasse splays was the most important feature affecting coal body size and geometry.
(UnM)AAI8022373
Source: Dissertation Abstracts International, Volume: 41-04, Section: B, page: 1283.
Thesis (Ph.D.)--University of South Carolina, 1980.
Microfiche.
Keywords: Geology